On the Ruins of the Future: scientists in the Argentine fiction of the last decade - Ezequiel De Rosso (Zama. Revista del Instituto de Literatura Hispanoamericana, 2019)
This paper proposes the hypothesis that in the last decade of Argentinian literature scientific research coccupies a privileged spot only comparable to the one it occupied by the end of XIXth century. Building on the analysis of Roque Larraquy y Diego Ontivero’s Informe sobre ectoplasma animal, Pablo Marquevichi’s El archivo del honorable Doctor Rudolf Wolgang Gerhard and Pola Oloixarac’s Las constelaciones oscuras it poses that these texts originality lies in a new disciplinary configuration of fiction.